A comparison of in situ leaf photosynthesis and chlorophyll fluorescence at the top canopies in rainforest mature trees - Ishida, A.; Toma, T.; Marjenah (2005)
Tropical tree species are divided into two principal groups, climax (or shade-tolerant) and pioneer (or light demanding) tree species. The top canopy leaves of mature trees are exposed to high solar radiation, regardless of whether they are climax or pioneer trees. This article compares leaf physiology and morphology at the top canopies of a climax Dipterocarpus corunutus tree and a pioneer Macaranga gigantea tree in a rainforest, East Kalimantan. Their data indicate low light-use capacity and high susceptibility for excess light energy of photosystem II in D. cornutus. The leaf properties were different between the mature climax and pioneer trees, even if their leaves grew under similar light environments at the top canopies.